Risk‐aware last‐minute data backup in inter‐datacenter networks. Issue 5 (1st September 2019) - Das, Shrayan; Panda, Kirtan Gopal; Sen, Debarati; Arif, Wasim
Abstract : Network failure caused by disasters (both natural and man‐made like earthquakes, floods, cyclones, electromagnetic pulse attacks etc.) result in communication disruption and huge amounts of data loss in the backbone datacenter (DC) networks. To prevent such large‐scale network disruptions and quickly resume connectivity after the disaster, network operators require improved and efficient data‐transfer algorithms in geographically distributed (geo‐distributed) optical inter‐DC networks. Minimising loss of infrastructure and preventing network disruption requires estimating the damage from a possible disaster. In this study, the authors consider a mutual backup model, where DCs can serve as backup sites of each other, thereby significantly reducing the backup duration (i.e. DC‐Backup‐Window (DC‐B‐Wnd)). They specifically consider the joint optimisation of probabilistic backup site selection and the amount of data to be backed up. They propose mixed‐integer linear programming models for backup time minimisation using a single DC as well as dual DCs at backup sites. Further, they investigate the trade‐off between DC‐B‐Wnd and the computational complexity of the proposed algorithms and perform extensive numerical simulations to show that, in the case of disasters, single and dual DC backups with risk‐aware probabilistic path selection give shorter backup windows as compared to existing algorithms.